Political, social and religious causes of discord between Muslims and polytheists in the Meccan period of Islamic history (Journal of Philosophy Culture and Political Science, 2015)
The origin of Islamic religion on the Arabic peninsula became a reason of appearance of religious contradictions between supporters multidivine and by the followers of prophet of Muhammad (p.b.u.h.) In spite of the fact that primary cause of conflict is name opposition of religious persuasions, it is necessary to mark circumstance that intensifying of situation has the historical, cultural and economic hidden motive. This interconfessional conflict gradually outgrew in political opposition. History testifies that proponent in a political plan the tribe of kuraish-mushriks was applied by economic approvals in regard to the Muslims of Mecca. In rows Muslims there were many representatives of unprotected layers of society, therefore at first they forced to come running to the help of such traditional concepts of Arabic society as tribalism. The move of Muslims to Ethiopia became beginning of establishment of international relations and interconfessional dialogue.Key words: Muhammad, Mecca, Kuraish, sanctions, interreligious dialogue, Islamic state, Akaba, Christians, Zoroastrianism.